FISHERMAN EMPOWERMENT PROGRAM IN TALAUD ISLANDS - Mamentu, Michael; Rares, Joyce Jacinta; Isa, Rusli (Public Policy Journal, 2023)
Talaud Islands Regency is a regency in the province of North Sulawesi located on the border of Indonesia and the Philippines. This area has enormous fisheries potential, characterized by high illegal fishing activities by foreign fishermen in the region. Most of the fish sold in the central fish market in General Santos (Philippines) comes from these islands. The government has implemented various special stimulus programs to empower traditional fishermen, but the poverty rate of fishermen in the region has not changed significantly. The study was conducted in two stages. The first stage is to try to find the right methods to empower fishermen in the region so that they have better socioeconomic skills. The second stage is to implement an empowerment model that will make the socio-economic quality of targeted traditional fishermen will increase. The results of the study found that the cause of significant changes in the quality of social and economic life of fishermen (small fishing), rooted in the power of nepotism in the implementation of the policy. Fishermen empowerment policies in the form of fresh financial assistance and marine infrastructure, are given to the wrong targets. Assistance is not given to small fishing groups but established fishing individuals (boat owners "pajeko"), or in other communities (artisans and farmers) who do not work as fishermen. In conclusion, it is urgently needed to change the behavior of decision makers, especially those responsible for improving the quality of life of small fishermen.